The scrutiny of geomorphologic effects of Armaghankhane and Taham faults - gholam hassan jafari; Asghar rostamkhani (تحقیقات کاربردی علوم جغرافیایی)
One of the unique properties of northern landforms of zanjanrood catchment is having smooth surfaces that have been interrupted by deep valleys. Rivers that don’t have a wide catchment upper their front mount are running in parallel deep valleys that the topographical situations don’t let them to receive around surface runoffs. This situation has made them to move in parallel form and not to join with each other. In some parts of sub basins, the water dividing line had been incorporated with the beach of main river valley (Sohrein River). The extent of catchments upper the mount front is not in a situation that let to dig valleys that sometimes exceeded to hundreds meters deep. These valleys had kept their primary height differences than it’s around. According to these properties, the style of formation and their evolution was considered as a geomorphological point. To get the answer, topographic and geologic maps and satellite images was made, and traced the geomorphologic effects of faults and corrected in different field works. Evaluation of tectonic activity in area, have been estimated by using Morphtectonics indicators of asymmetric factor (Af), integral hypsometric curve (Hi), valley floor width-to-height ratio (Vf) and transverse topographic (T). Relative Active Tectonics Index (LAT) showed the whole basin high activity (class2). Based on the Af index uplift have been attributed to the right bank in Sohrin and Sarmsaqlv basins and in Qracharian sub-basin to the left bank. Which states that the center of Neotectonic power center located in the place between the three sub-basins?